Memorandum of understanding between Universiti Teknologi MARA, Malaysia and Universitas Negeri Yogyakarta, Indonesia / Fakulti Pendidikan - Universiti Teknologi MARA, Fakulti Pendidikan (Universiti Teknologi MARA (UiTM), 2018)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.